Physicochemical characterisation, digestibility and anticonstipation activity of some high‐resistant untraditional starches from zingiberaceae plants. (8th January 2017) - Mao, Xinhui; Huang, Hanhan; Li, Xia; Wang, Tingting; Chen, Xuetao; Gao, Wenyuan
Summary: To find new starch sources with particular characteristics, five untraditional starches from zingiberaceae plants were studied about their physicochemical properties, digestibility and anticonstipation activity and compared with starches from traditional sources (potato and corn). All the five starches presented the shape of triangular, with visible thin sheet, which were significantly different from conventional sources. The crystal type of these five starches was B‐type pattern. Swelling power at 75 °C was negatively correlated with crystallinity. There was no significant difference in amylose content between starches from rhizome and tuber of Curcuma phaeocaulis Val., while they displayed significant variability in RS content. Starches from rhizome of Curcuma kwangsiensis, Curcuma wenyujin, Curcuma phaeocaulis Val. and Curcuma longa L. possessed much higher resistant starch content (range from 87.06% to 95.40%) and could better prevent constipation than potato and corn starches, which made them potential for managing diabetes and improving defecation conditions. Abstract : Five untraditional starches from zingiberaceae plants were studied about their physicochemical properties, digestibility and anticonstipation activity and compared with starches from traditional sources (potato and corn).